2023
DOI: 10.3926/jotse.1742
|View full text |Cite
|
Sign up to set email alerts
|

Uses of Facebook and academic procrastination in general studies students at a Peruvian university

Alicia Taipe,
Yulissa Heredia,
Osbaldo Turpo - Gebera
et al.

Abstract: The incidence of consumption on Facebook around the world and its implications for university students is something that has necessarily been studied in the scientific literature (Gil et al., 2019). Fewer and far between are works focused on the study of social networks and academic procrastination in a population, particularly with a non-traditional teaching methodology (General Studies), even though this knowledge would allow us to obtain a profile of university students and identify their possible actions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
1
0
1
Order By: Relevance
“…Even among the general studies focusing on students' Facebook use, there is a disagreement in the findings reported across different studies. For example, some studies show that students used Facebook to a low extent (Gordon et al, 2023;Palazon et al, 2015;Taipe et al, 2023). In contrast, others have shown that students' use of Facebook was high (Ilakkuvan et al, 2019), especially for viewing sexual content (Langlais et al, 2020;Stănculescu & Griffiths, 2021;Owan et al, 2020), narcissism, self-identity and empowerment (Gulatee et al, 2021), and other non-educational purposes (Zagidullin et al, 2021).…”
Section: Facebook Use Among Higher Education Studentsmentioning
confidence: 99%
“…Even among the general studies focusing on students' Facebook use, there is a disagreement in the findings reported across different studies. For example, some studies show that students used Facebook to a low extent (Gordon et al, 2023;Palazon et al, 2015;Taipe et al, 2023). In contrast, others have shown that students' use of Facebook was high (Ilakkuvan et al, 2019), especially for viewing sexual content (Langlais et al, 2020;Stănculescu & Griffiths, 2021;Owan et al, 2020), narcissism, self-identity and empowerment (Gulatee et al, 2021), and other non-educational purposes (Zagidullin et al, 2021).…”
Section: Facebook Use Among Higher Education Studentsmentioning
confidence: 99%
“…Es preciso mencionar que para obtener el logro de competencias es necesario citar la bibliografía existente sobre el "aprendizaje estratégico" el cual tiene sus cimientos en la basada en la "teoría de la psicología cognitiva", la misma que incluye el procesamiento de la información (Weinstein, 1989), asimismo tiene sus bases en la teoría del aprendizaje autorregulado (Zimmerman, 2000;Zimmerman, 2002;Zimmerman et al, 2017); estas teorías conciben el aprendizaje académico como efectivo e independiente, el cual trasciende hasta la metacognición, motivación intrínseca y acciones estratégicas; por otro lado, también concierne a la "teoría socio-cognitiva" la misma que explica lo intrincado de los procesos de la conducta humana, sustenta que a través de la observación los seres humanos pueden aprender lo que acarrea una determinada acción y a su vez aprender de sus consecuencias, seguido de ello la persona discierne y opta por llevarla a cabo o evitarla, ahora bien esto estará sujeto a las características individuales y sobre todo su grado de motivación, desde esa perspectiva, las personas aprenden de los demás al relacionarse con sus semejantes (Bandura y Walters, 1973;Taipe et al 2023).…”
Section: Introductionunclassified